Family Profile and its Relation to the Growth of Toddlers 36-59 Months in Palembang City - Amrina Rosyada; Mawaddah Dyah Popita (Jurnal Ilmu Kesehatan Masyarakat, 2023)
The toddler period is a golden period or golden age. At the age of 0-5 years, the growth and development of the toddler's brain increases rapidly. Growth is related to changes in size, quantity, or size that can be measured in units of weight (grams, kilograms) and units of length (centimeters, meters). What affects toddlers' growth can come from the family and the environment. This research aims to analyze to analyze the relationship between family profiles and characteristics with the growth of toddlers 36-59 months in Palembang City. A cross sectional method was conducted on 148 respondents from mothers of toddlers aged 36-59 months in Palembang City, and the sample collection method used cluster sampling. The results showed there are six factors that affect the growth of children under five:  The father's smoking status, milk formula, breakfast habits, the child's gender, the mother's occupation, and the influence of the mother's knowledge. The most dominant factor affecting children's growth is the habit of breakfast with Prevalence Risk 5.833, which means that toddlers who have no habit have a growth risk of 5.833 times to experience abnormality compared to toddlers who have breakfast habits after controlling for variables such as father smoking status, milk formula, child gender, mother’s occupation, and mother's knowledge.